PIMS ù The Road to Efficient, Cost-Effective Plant Operation - D Hunter (The Australasian Institute of Mining and Metallurgy, 2003)
A production information management system (PIMS) was recently implemented at Queensland NickelÆs Yabulu Refinery. Although a strong business case was developed to justify the significant investment in PIMS some potential beneficiaries remained sceptical of the anticipated benefits. The decision to install PIMS was justified as the on-line availability of continuous production data enabled the optimisation of some crucial operations resulting in significant cost savings, improved throughput and final product quality. Furthermore the rapid access to extended historical data has allowed the cause of repeated failure of equipment to be determined. The investment is expected to pay for itself within two years and has already contributed towards significant savings. This paper focuses on some of the diverse production improvements gained and compares the anticipated benefits in the business case to those achieved. A brief outline of the phased implementation of the OSIsoft PI data historian and complementary client software at Yabulu is included, along with details of the lessons learned.